2008
DOI: 10.1007/s10096-008-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic impact of blood culture practices and antibiotic consumption on pneumococcal bacteraemia in children

Abstract: This study examined the roles of two different diagnostic approaches to children with fever of unknown origin in determining the patterns of pneumococcal bacteraemia in two Spanish regions by comparing their main epidemiologic characteristics. Whereas a blood culture is routinely obtained in this setting in Navarre, this is not generally the case in Majorca. Additionally, the potential role of antibiotic consumption in each region was also analysed. Cumulative incidences in children under the age of 14 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…This importance would be even higher in other areas of our country where 19A is highly prevalent [ 18 - 20 ]. IPDs caused by serotype 19A were not found in a previous study in 2003-4 in Majorca [ 21 ], and in our series they only represented 7.6% of all IPDs. Probably a low prevalence of serotype 19A in Majorca made this serotype non-selectable by PCV7 use.…”
Section: Discussioncontrasting
confidence: 78%
“…This importance would be even higher in other areas of our country where 19A is highly prevalent [ 18 - 20 ]. IPDs caused by serotype 19A were not found in a previous study in 2003-4 in Majorca [ 21 ], and in our series they only represented 7.6% of all IPDs. Probably a low prevalence of serotype 19A in Majorca made this serotype non-selectable by PCV7 use.…”
Section: Discussioncontrasting
confidence: 78%
“…Due to clinical practice, this issue would be most pronounced in studies of young children in emergency departments, and less pronounced, though perhaps still relevant, in studies of hospitalized patients. On the other hand, reports from Spain have indicated that both the rate of blood-culturing and reporting of IPD have increased since the introduction of the vaccine, and if not properly accounted for, they could make replacement appear more significant than it is [4344]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies from Spain have examined the issue, with some areas reporting complete serotype replacement with no net effect of the vaccine on IPD incidence [5, 5455] while another reported no increase in NVTs [56]. The Spanish data are further complicated by regional differences in blood culturing practices and by increases in blood culturing and reporting rates since the introduction of PCV7 [4344, 57]. In France, the vaccine had no overall effect in the most recent national study of pediatric meningitis in children under 5, though it showed a benefit in those under 2 [58].…”
Section: Introductionmentioning
confidence: 99%
“…Use of the vaccine has increased from 2002 onwards, with reported vaccine coverage in 2006 below 50%, assuming complete vaccination schedules (13). Selective PCV7 vaccination has resulted in a low impact in the incidence of IPD in children in Spain (2,21) given the intermediate vaccination coverage achieved and the increase in disease detection that has occurred over that time (22). In October 2006, the Autonomous Region of Madrid approved its inclusion in the childhood vaccination calendar, carrying out necessary clinical and serotype surveillances to update IPD changes with universal pediatric vaccination.…”
mentioning
confidence: 99%